Further evidence that the KIAA0319 gene confers susceptibility to developmental dyslexia. - Harold, D; Paracchini, S; Scerri, T; Dennis, M; Cope, N; Hill, G; Moskvina, V; Walter, J; Richardson, A; Owen, M; Stein, J; Green, E; et al. (2006)
The DYX2 locus on chromosome 6p22.2 is the most replicated region of linkage to developmental dyslexia (DD). Two candidate genes within this region have recently been implicated in the disorder: KIAA0319 and DCDC2. Variants within DCDC2 have shown association with DD in a US and a German sample. However, when we genotyped these specific variants in two large, independent UK samples, we obtained only weak, inconsistent evidence for their involvement in DD. Having previously found evidence that variation in the KIAA0319 gene confers susceptibility to DD, we sought to refine this genetic association by genotyping 36 additional SNPs in the gene. Nine SNPs, predominantly clustered around the first exon, showed the most significant association with DD in one or both UK samples, including rs3212236 in the 5' flanking region (P = 0.00003) and rs761100 in intron 1 (P = 0.0004). We have thus refined the region of association with developmental dyslexia to putative regulatory sequences around the first exon of the KIAA0319 gene, supporting the presence of functional mutations that could affect gene expression. Our data also suggests a possible interaction between KIAA0319 and DCDC2, which requires further testing.